Gene expression signatures differ with extent of atherosclerosis in monkey iliac artery - Eyster, Kathleen M. (2011)
OBJECTIVE: To evaluate global gene expression patterns in the common iliac arteries of monkeys with varied extent of atherosclerosis. METHODS: The left common iliac artery was removed from ovariectomized cynomolgus monkeys (n=12) after 6.5 years of consuming a diet containing fat and cholesterol at levels comparable to that consumed in western populations. Arterial gene expression was analyzed by DNA microarray and real time RT-PCR. RESULTS: Significant differential expression of 986 genes was observed in iliac arteries containing moderate to large atherosclerotic plaques compared to normal/minimally affected reference group arteries. Atherosclerosis-associated genes included cytokines, chemokines, components of signal transduction pathways, and transcriptional activators and repressors, as well as other functional categories. Real time RT-PCR confirmed differential expression of genes chosen from a variety of functional categories. Specifically, expression of genes for estrogen receptor 1 (ESR1), claudin 11, and BH protocadherin 7 (PCDH7) were reduced, whereas expression of genes for apolipoprotein E (ApoE), growth differentiation factor 15 (GDF15), superoxide dismutase 2 (SOD2), SET domain, bifurcated 2 (SETDB2), phospholipase A2 group IIA (PLA2IIA), phospholipase A2 group VII (PLA2VII), and ring finger protein 149 (RNF149) were increased in atherosclerotic arteries. CONCLUSIONS: The gene expression environment in arteries containing atherosclerotic plaques is profoundly different from that of relatively unaffected arteries and reflects the cellular and molecular complexity of atherosclerosis and associated arterial remodeling processes.